Figurative Languages and Their Meaning Found in the Rachael Lippincott’s Novel Five Feet Apart - Salsabila, RR Tahta Ni'mah; Sudar, Sudar; Nugraeni, Ismawati Ike (Scripta : English Department Journal, 2024)
This research seeks to identify the forms of figurative language present in Rachael Lippincott’s novel Five Feet Apart and to explain the meanings of the identified figurative language. This research employed a qualitative methodology. The primary instrument was the researcher herself. The researcher employed the content analysis methodology. The study indicates that five forms of figurative language exist out of twelve, according to Perrine’s theory. The figures of speech include personification, metaphor, exaggeration, metonymy, and simile. Personification constitutes the predominant form of figurative language, appearing in 27 of the 69 phrases. The preval___ent sort of figurative language in the novel is personification, which plays a crucial role in expressing the meanings of various figurative expressions. The novel explores the emotions (fear, anxiety, pain, anger, joy) experienced by the characters in the novel.